Sistem Pendukung Keputusan untuk Rekomendasi Wirausaha Menggunakan Metode AHP-TOPSIS (Studi Kasus Kab. Probolinggo) - Ghulam Mahmudi Al Azis; Imam Cholissodin; Muhammad Tanzil Furqon (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Along with the growing number of Indonesian population, also raises the competition in looking for work. The limited job vacancy impacts the increasing number of unemployed every year. Until February 2016, the labor force in Indonesia reached 127 million people with an overall unemployment rate of 5.5% or 7 million people. To overcome this increasing number of unemployment, needed step solution that is in the form of decision support for entrepreneurship. Decision support systems can be used to recommend an entrepreneur for unemployment or everyone. AHP method and TOPSIS method is one of the methods of decision support system that can be combined with calculating the weight of criterion using AHP method then continued by calculating the value of preference for ranking from entrepreneurial alternative using TOPSIS method. The AHP-TOPSIS method will recommend the results of 3 entrepreneurs with the highest preference value. In accordance with the test results, that these application can help to recommend entrepreneurs in helping decisions support for user to choose an entrepreneur.